2006
DOI: 10.1002/ijc.21779
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of orotate phosphoribosyl transferase among 5‐fluorouracil metabolic enzymes in resectable colorectal cancers treated by oral 5‐fluorouracil‐based adjuvant chemotherapy

Abstract: Orotate phosphoribosyl transferase (OPRT) is the main enzyme that involves in phosphoribosylation of 5-fluorouracil (5-FU), an essential step that leads to tumor growth inhibition. In our study, the prognostic relevance of OPRT, thymidylate synthase (TS) and dihydropyrimidine dehydrogenase (DPD) in resectable colorectal cancer (CRC) patients treated by oral 5-FU were compared to further clarify the prognostic value of OPRT. Tumor tissue was collected from 90 CRC patients and the patients were followed for 5.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…To our knowledge, the present study was the first clinical report using immunohistochemistry, to demonstrate the clinical significance of the OPRT expression in a relatively large number of cancer patients treated with UFT. In fact, a recent clinical study also revealed a positive OPRT activity to be associated with a better prognosis in resectable colorectal cancer patients treated with oral 5-FU (Ochiai et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, the present study was the first clinical report using immunohistochemistry, to demonstrate the clinical significance of the OPRT expression in a relatively large number of cancer patients treated with UFT. In fact, a recent clinical study also revealed a positive OPRT activity to be associated with a better prognosis in resectable colorectal cancer patients treated with oral 5-FU (Ochiai et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…As to the methodology of 5-FU metabolic pathway enzymes, protein activity, immunohistochemistry, enzymelinked immunosorbent assay (ELISA) and mRNA levels have been reported (13)(14)(15). Concerning the routine measurement of these enzymes, protein activity measurements are not technically feasible because of the complexity in the use of radioisotopes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a high-expression level of TS and low-expression levels of DPD were correlated with poor prognosis (13,14). In contrast, it has been reported that OPRT, though not TS and DPD have a prognostic value in patients treated with 5-FU-based adjuvant chemo-therapy (15). It was thought that one of the reasons for these confused results is the purity of tumor samples.…”
Section: Introductionmentioning
confidence: 99%
“…This result may support Grothey's report in dual responders. Several studies have investigated individualization in 5-FU-based chemotherapy based on the 5-FU metabolism-associated enzymatic and genetic characteristics of the individual patient (22)(23)(24)(25)(26)(27)(28)(29). In addition, the individualization of 5-FU-based chemotherapy based on the serum 5-FU concentration has been reported lately (30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%